2019
DOI: 10.1007/s00394-019-01913-w
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and differences of dietary and other determinants of iodine status in pregnant women from three European birth cohorts

Abstract: Acknowledgements EUthyroid project: This project has received funding from the European Union´s Horizon 2020 research and innovation programme under grant agreement No 634453. ALSPAC: We are extremely grateful to all the families who took part in this study, the midwives for their help in recruiting them, and the whole ALSPAC team, which includes interviewers, computer and laboratory technicians, clerical workers, research scientists, volunteers, managers, receptionists and nurses. The UK Medical Research Coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 70 publications
(88 reference statements)
3
25
2
1
Order By: Relevance
“…In another study in China the type of dietary salt, maternal age, occupation, consumption of complementary micronutrients and seafood were found to affect urinary iodine meaningfully [32]. In another study by Dineva et al seafood consumption, iodinated salt intake and maternal age were found to be defining factors in urinary iodine concentration of the mother [33]. However, this study did not find any relation of statistical significance between maternal iodine deficiency and maternal complications of the pregnancy.…”
Section: Discussioncontrasting
confidence: 57%
“…In another study in China the type of dietary salt, maternal age, occupation, consumption of complementary micronutrients and seafood were found to affect urinary iodine meaningfully [32]. In another study by Dineva et al seafood consumption, iodinated salt intake and maternal age were found to be defining factors in urinary iodine concentration of the mother [33]. However, this study did not find any relation of statistical significance between maternal iodine deficiency and maternal complications of the pregnancy.…”
Section: Discussioncontrasting
confidence: 57%
“…Similarly, in a study where pregnant women from three large cohorts in Europe were included, intake of milk and dairy products was the main dietary determinant of iodine status. Other dietary determinants were fish and shellfish and cereals (Dineva et al, 2020). Breastfeeding gave significantly reduced odds of having UIC above 100 μg/L in our study, which is not unexpected because large amounts of iodine are secreted into breast milk (Laurberg & Andersen, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Participants who reported the use of thyroid medication during pregnancy were excluded. Variables to be included in the models were chosen on a theory‐based approach and consisted of covariates known from previous studies to influence iodine status in pregnancy (Dineva et al, 2020; Henjum, Aakre, et al, 2018; Henjum et al, 2017). For iodine supplement use, an unadjusted model, then a model adjusted for maternal age, parity, breastfeeding status, time and time*supplement use was performed.…”
Section: Methodsmentioning
confidence: 99%
“…The use of flexible modeling and various sensitivity analyses excludes that skewness of the data caused by values above 300 µg/g affected would affect our results. Although we had incomplete data on iodine supplement use in two of the three cohorts (7), high values of the UI/Creat in our study population do not necessarily reflect iodine supplement use. For example, it is unlikely that British pregnant women in the early 1990s would have taken iodine-containing supplements as there was, and still is, no legislation concerning iodine nutrition in the UK.…”
Section: Accepted Manuscriptmentioning
confidence: 87%